Pendidikan Multikultural untuk Pembentukan Karakter Anak: Membangun Jembatan Harmoni Antarbudaya di Era Kontenporer - Darmawan, Wawan; Mbura, Ewilensia Magdalen (Visi Sosial Humaniora, 2024)
iIn today's increasingly complex global society, multicultural education has become a key focus in shaping children's inclusive and empathetic characters. This article explores the important role of multicultural education in shaping children who can appreciate cultural diversity and promote tolerance and cross-cultural understanding. Using a holistic and interactive approach, the article highlights effective educational strategies and practices to enrich children's learning experiences, facilitate intercultural dialogue, and address inequality and discrimination. The research employs literature review and case studies to investigate the impact and implementation of multicultural education practices in the context of children's character formation. By integrating multicultural values into the curriculum, creating inclusive learning environments, and actively engaging the community, multicultural education can serve as a solid foundation for building harmonious intercultural relationships.